2018
DOI: 10.21037/gs.2018.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing large volume fat grafting in breast reconstruction after nipple sparing mastectomies

Abstract: Nipple sparing mastectomy (NSM) has gained popularity especially in prophylactic mastectomies allowing improved cosmetics. Traditionally reconstruction has utilized implants or autologous tissue. With the development of large volume fat grafting additional reconstructive techniques can be utilized in NSM reconstruction. This can either complement a technique or be a standalone form of reconstruction. This paper is intended to serve as a broad overview of fat grafting and its potential role in reconstructing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…11 Favorable patient satisfaction outcomes have been proposed with the adjunctive use of autologous fat grafting in patients who undergo IBR after mastectomy. 29,30 In 2017, Qureshi et al conducted a prospective cohort study to evaluate patient-report satisfaction with aesthetic outcomes in patients who underwent direct implant (DTI) placement versus implant placement after tissue expansion (TE/I). The authors found that patients within the TE/I patient cohort who underwent fat grafting reported higher BREAST-Q scores compared with those undergoing TE/I reconstruction without fat grafting (87 AE 17 vs. 66 AE 12; p ¼ 0.02).…”
Section: Submuscular Breast Reconstructionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Favorable patient satisfaction outcomes have been proposed with the adjunctive use of autologous fat grafting in patients who undergo IBR after mastectomy. 29,30 In 2017, Qureshi et al conducted a prospective cohort study to evaluate patient-report satisfaction with aesthetic outcomes in patients who underwent direct implant (DTI) placement versus implant placement after tissue expansion (TE/I). The authors found that patients within the TE/I patient cohort who underwent fat grafting reported higher BREAST-Q scores compared with those undergoing TE/I reconstruction without fat grafting (87 AE 17 vs. 66 AE 12; p ¼ 0.02).…”
Section: Submuscular Breast Reconstructionmentioning
confidence: 99%
“…The additional use of fat grafting to the traditional method of implant placement has favorable aesthetic outcomes from both the surgeon's and patient's perspective. 29,30…”
Section: Submuscular Breast Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations